2014
DOI: 10.5152/eurjrheumatol.2014.037
|View full text |Cite
|
Sign up to set email alerts
|

Etanercept in the treatment of SAPHO syndrome: Which place?

Abstract: Synovitis, acne, pustulosis, hyperostosis, and osteitis syndrome (SAPHO) is a rare disease combining skin, bone, and joint manifestations. Its treatment remains a debated issue in the absence of a valid therapeutic strategy. The experience with tumor necrosis factor alpha (TNF alpha)-blocking agents is still small but encouraging. This therapy is reserved for refractory cases. The most commonly used agent is infliximab. Only few cases treated by etanercept have been reported in the literature. We report a new … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Bisphosphonates, which inhibit bone resorption and turnover, are frequently used as disease modifiers and anti-inflammatory agents for SAPHO syndrome [12]. Amital et al reported that pamidronate appeared to be a very effective therapy for patients with SAPHO syndrome because it promoted remission in all affected body parts, such as the bone, joint, and skin, and ceased the bouts that characterized [13]. In patients failing anti-TNF alpha agents, IL-1 inhibitors could be an effective therapy [14].…”
Section: Discussionmentioning
confidence: 99%
“…Bisphosphonates, which inhibit bone resorption and turnover, are frequently used as disease modifiers and anti-inflammatory agents for SAPHO syndrome [12]. Amital et al reported that pamidronate appeared to be a very effective therapy for patients with SAPHO syndrome because it promoted remission in all affected body parts, such as the bone, joint, and skin, and ceased the bouts that characterized [13]. In patients failing anti-TNF alpha agents, IL-1 inhibitors could be an effective therapy [14].…”
Section: Discussionmentioning
confidence: 99%